Impact on vehicle fuel economy of the soot loading on diesel particulate filters made of different substrate materials. (15th June 2015) - Millo, Federico; Andreata, Maurizio; Rafigh, Mahsa; Mercuri, Davide; Pozzi, Chiara
Abstract: Wall flow DPFs (Diesel Particulate Filters) are nowadays universally adopted for all European passenger cars. Since the properties of the filter substrate material play a fundamental role in determining the optimal soot loading level to be reached before DPF regeneration, three different filter material substrates (Silicon Carbide, Aluminum Titanate and Cordierite) were investigated in this work, considering different driving conditions, after treatment layouts and regeneration strategies. In the first step of the research, an experimental investigation on the three different substrates over the NEDC (New European Driving Cycle) was performed. The data obtained from experiments were then used for the calibration and the validation of a one dimensional fluid-dynamic engine and after treatment simulation model. Afterward, the model was used to predict the vehicle fuel consumption increments as a function of the exhaust back pressure due to the soot loading for different driving cycles. The results showed that appreciable fuel consumption increments could be noticed only in particular driving conditions, and, as a consequence, in most of the cases the optimal filter regeneration strategy corresponds to reach the highest soot loading that still ensures the component safety even in case of uncontrolled regeneration events. Highlights: Three different substrate materials for a Diesel Particulate Filter were investigated. Fuel consumption increases due to DPF soot loading were generally not appreciable. Optimal soot loading before regeneration was the highest safeguarding DPF integrity. SiC substrate showed highest soot load limit and lowest fuel consumption penalties. AT and Cd substrate properties lead to lower soot load limits than SiC.